Let x=2+u, y=v-1 then dx=du, dy=dv and x+y-1=u+v.
With this substitution we have a homogenous equation:
udu + 4(u+v)dv = 0
du/dv = -4(1+v/u)
The standard substitution commonly used for this type of ODE is:
s=u/v
Then u=sv, du/dv = s+v ds/dv, v/u = 1/s and the equation will be
s + v ds/dv = -4(1 + 1/s)
This is an equation with separable variables. We write it as follows:
"- \\frac{dv}{v} = \\frac{ds}{s + 4 +4\/s} = \\frac {s ds}{(s+2)^2} = (\\frac{1}{s+2}-\\frac{2}{(s+2)^2})ds = d(\\ln|s+2| +\\frac{2}{s+2})"
"d(\\ln|v(s+2)| +\\frac{2}{s+2})=0"
"\\ln|v(s+2)| +\\frac{2}{s+2}=c"
In the original variables:
"\\ln|x+2y| +\\frac{2}{2+(x-2)\/(y+1)}=c"
"\\ln|x+2y| +\\frac{2y+2}{2y+x}=c"
"|x+2y| e^{\\frac{2y+2}{2y+x}}=e^c"
Further simplification is hardly possible.
The function "(x+2y) e^{\\frac{2y+2}{2y+x}}" is the first integral of the ODE.
In particularly, y=-x/2 is one of the integral curves of this ODE.
Comments
Leave a comment